1999
DOI: 10.1111/j.1749-6632.1999.tb07682.x
|View full text |Cite
|
Sign up to set email alerts
|

MMP Inhibition in Abdominal Aortic Aneurysms: Rationale for a Prospective Randomized Clinical Trial

Abstract: Abdominal aortic aneurysms (AAAs) represent a chronic degenerative condition associated with a life-threatening risk of rupture. The evolution of AAAs is thought to involve the progressive degradation of aortic wall elastin and collagen, and increased local production of several matrix metallo-proteinases (MMPs) has been implicated in this process. We have previously shown that tetracycline derivatives and other MMP inhibitors suppress aneurysm development in experimental animal models of AAA. Doxycycline also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
101
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 170 publications
(104 citation statements)
references
References 81 publications
2
101
0
1
Order By: Relevance
“…Although the vast majority of these lesions are small and asymptomatic, their natural history is characterized by progressive growth and eventual rupture. Recognition that different MMPs participate in the pathobiology of AAAs has fostered the notion that these enzymes might be useful therapeutic targets in this disease, providing a novel approach to reduce the degradation of fibrillar proteins responsible for maintaining aortic wall tensile strength and potentially suppressing the rate of aneurysm expansion (39). The present study provides new experimental evidence in support of this concept and suggests that strategies targeting MMP-9 might be a particularly fruitful avenue for further investigation.…”
Section: Discussionsupporting
confidence: 52%
“…Although the vast majority of these lesions are small and asymptomatic, their natural history is characterized by progressive growth and eventual rupture. Recognition that different MMPs participate in the pathobiology of AAAs has fostered the notion that these enzymes might be useful therapeutic targets in this disease, providing a novel approach to reduce the degradation of fibrillar proteins responsible for maintaining aortic wall tensile strength and potentially suppressing the rate of aneurysm expansion (39). The present study provides new experimental evidence in support of this concept and suggests that strategies targeting MMP-9 might be a particularly fruitful avenue for further investigation.…”
Section: Discussionsupporting
confidence: 52%
“…30 The protective effect of MMP-9 and MMP-12 deficiency against atherosclerotic media degradation and accompanying ectasia and aortic dilatation suggests that these particular MMPs may play a central role in aneurysm formation since elastin degradation and aortic diameter expansion are hallmarks of this disease. 10 In regard to MMP-9, its involvement in aneurysm progression was additionally supported in 2 inflammatory models of AAA. 14, 15 The latter studies and our studies in concert argue for MMP-9, and possibly MMP-12, as potential targets to prevent aneurysm expansion before it reaches a critical size, leading to life-threatening ruptures.…”
Section: Discussionmentioning
confidence: 95%
“…7,8 In addition, tetracycline derivatives and synthetic MMP inhibitors suppressed experimental AAA. 9,10 We showed that urokinasetype plasminogen activator, in part by activation of MMPs, was essential for atherosclerotic media destruction. 11 However, none of these studies clarified a direct role for individual MMPs.…”
mentioning
confidence: 99%
“…However, direct assessment of MMP-9 as a cause of cigarette smokeinduced emphysema has been lacking. Because Food and Drug Administration approved, commercially available compounds (e.g., doxycycline) can decrease MMP-9 activity at achievable systemic concentrations (39,40), we decided to evaluate MMP-9 in the mouse smoking model and human monocytes and alveolar macrophages. We now demonstrate that MMP-9 deletion in mice does not prevent either cigarette smoke-induced lung inflammation or cigarette smoke-induced airspace enlargement.…”
Section: Discussionmentioning
confidence: 99%